The mediating role of self-compassion and the moderating role of restrictive emotionality in gender role discrepancy and depression - Maya Kagan; Michal Mahat-Shamir (Heliyon, 2023)
Masculine gender role discrepancy is men's perception of themselves as people who fail to conform to traditional masculine norms. There is solid scientific evidence that gender role discrepancy is related to grave mental health outcomes such as depression. Yet, the mechanisms that explicate the relationship between masculine gender role discrepancy and masculine depression remain unclear. As individual differences in men are suggested to be associated with depression, the current study aimed to examine the mediating role of self-compassion and the moderating role of restrictive emotionality in the association between masculine gender role discrepancy and masculine depression.For the purpose of the current study, a structured questionnaire was distributed through online means, resulting in a sample of 954 men aged 18 and older. The results revealed that self-compassion partially mediates the relationship between gender role discrepancy and masculine depression. Moreover, a positive effect of gender role discrepancy on masculine depression was found to be more pronounced at higher levels of restrictive emotionality. The contemporary empirical evidence underscores the significance of individual variances in adhering to conventional masculine gender norms concerning the nexus between gender role discrepancy and masculine depression. Moreover, this research accentuates the salience of gender role matters in shaping the mental well-being of men.